Exploring the Evolution and Challenges of Digital Media in the Cultural Value of Dunhuang Frescoes - Chen , Si; Vermol , Verly Veto; Ahmad, Hasma (Journal of Ecohumanism, 2024)
Leveraging digital communication, the rapid evolution of modern media technologies heralds unprecedented opportunities for the dissemination of this extraordinary artistic heritage. The emergence of digital technology, virtual reality, and social media has ushered in new platforms for the display of Dunhuang frescoes, presenting audiences with immersive encounters and interactive experiences. Harnessing these digital tools to illuminate the history, cultural meanings, and artistic nuances of Dunhuang frescoes has emerged as a compelling research frontier. Against this backdrop, this study embarks on an exploration of the contemporary state, challenges, and prospects of Dunhuang frescoes dissemination, guided by the lens of digital media evolution. By investigating the mechanisms of communication, the channels of digital media, and audience responses intricately woven into the fabric of Chinese Dunhuang frescoes art, the research aims to unearth the transformative impact of digital media technology on dissemination. Moreover, it seeks to unravel the intricate interplay of factors such as artists, audiences, and social contexts that shape the communication process. This research project is fueled by a trio of pivotal questions: What transformations do digital media evolution bring to the strategies of Dunhuang frescoes dissemination? How does digital media evolution influence the artistic representation of Dunhuang frescoes? What are the perceptions and experiences of audiences across various digital media platforms? Through qualitative research methods, triangulation, and oral narrative analysis, the study will delve into these questions, illuminating the evolving dynamics of Dunhuang frescoes art dissemination within the context of digital media evolution and artistic communication theories.